The filth of progress : immigrants, Americans, and the building of canals and railroads in the West - Dearinger, Ryan, 1979- (University of California Press, 2016)
"In America's historical imagination, toil and triumph against nature and overwhelming odds characterizes such achievements as the Erie Canal and the transcontinental railroad. Triumph transformed canal and railroad entrepreneurs into visionaries whose work brought the nation bountiful riches and did the Lord's bidding. Celebrated for their spirit and perseverance in 'building' the nation's infrastructure, they found respect for looking to tomorrow and creating a future. For generations, most indexes of American history supported and reinforced this narrative of progress. Yet, if this is the historical memory, it is conveniently stunted. What of those whose bodies strained and broke under the load of such glories? What of those men beyond the din and fanfare who only appear in old photographs with faces blurred and indistinguishable? In their lives and deaths in the mud, muck, and mountains is another history of American achievement. These barely visible and forgotten, ordinary men, 'unskilled' immigrants from Ireland and China, Mormons, and native-born American workingmen rank, as well, as the creators of national growth and progress. Their experiences and voices, along with those of the privileged and well-connected, are the subjects of this study. I examine the rise of Western canals and railroads to national prominence through the menial labor of countless men, largely hidden from view because they left virtually no paper trail, who strung together livelihoods at the economic fringes of society. This book examines the contest for control of American progress and history as distilled from the competing narratives of canal and railroad construction workers and those fortunate enough to avoid this fate"--Provided by publisher.